2021
DOI: 10.3390/jcm10163456
|View full text |Cite
|
Sign up to set email alerts
|

Do All Integrase Strand Transfer Inhibitors Have the Same Lipid Profile? Review of Randomised Controlled Trials in Naïve and Switch Scenarios in HIV-Infected Patients

Abstract: In this study, we aim to explore the effects on lipids of integrase strand transfer inhibitors (INSTIs) in naïve and switch randomised controlled trials, and compare them with protease inhibitors (PIs) and non-nucleoside reverse transcriptase inhibitors (NNRTIs). We reviewed phase 3/4 randomised clinical trials in the Cochrane and PubMed databases that compare an INSTI with a boosted PI, an NNRTI, or another INSTI plus one or two nucleoside/nucleotide reverse transcriptase inhibitors (NtRTIs) in naïve patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…In terms of the lipid profile, we observed a generally neutral effect on all serum lipids with no significant change from baseline. It is important to note that approximately half of the cohort were receiving an INSTI‐based regimen directly before BIC/FTC/TAF initiation, and – as previously reported – no changes are typically observed in lipids when switching between INSTIs [41]. Furthermore, since 28% of the study population were on a TDF‐based regimen directly before baseline, and given the fact that TDF has been previously reported to reduce lipid fractions [42], an increase in lipid parameters among people switching from TDF to TAF would have been expected but was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the lipid profile, we observed a generally neutral effect on all serum lipids with no significant change from baseline. It is important to note that approximately half of the cohort were receiving an INSTI‐based regimen directly before BIC/FTC/TAF initiation, and – as previously reported – no changes are typically observed in lipids when switching between INSTIs [41]. Furthermore, since 28% of the study population were on a TDF‐based regimen directly before baseline, and given the fact that TDF has been previously reported to reduce lipid fractions [42], an increase in lipid parameters among people switching from TDF to TAF would have been expected but was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Different ART regimens are associated with different risks for dyslipidemia. Several studies have shown that protease inhibitor-based ART was associated with increased risk for lipohypertrophy [10][11][12] ; lipoatrophy was more frequent with efavirenz than with lopinavir/r when combined with stavudine or zidovudine and less frequent when either drug was combined with tenofovir. 12,13 Integrase strand transfer inhibitors have neutral effect on lipids when compared with boosted protease inhibitor, efavirenz, and cobicistat-boosted elvitegravir (EVG/C) among antiretroviral-naive PLWH.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 27, 2022. ; https://doi.org/10.1101/2022.09.26.508302 doi: bioRxiv preprint after changing regimens from older protease inhibitors (86,96). Hypertension, another disorder related to lipid dysregulation, is also more prevalent in individuals receiving ART.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs despite the known impact of HIV on diminishing total cholesterol levels (86,(92)(93)(94)(95). Conversely other ARTs, including raltegravir, dolutegravir, and bictegravir, have either a beneficial or minimal impact on the cholesterol profile after changing regimens from older protease inhibitors (86,96). Hypertension, another disorder related to lipid dysregulation, is also more prevalent in individuals receiving ART.…”
Section: Discussionmentioning
confidence: 99%